Investigation of Siderophore-Promoted and Reductive Dissolution of Dust in Marine Microenvironments Such as Trichodesmium Colonies - Kessler, Nivi; Kraemer, Stephan M.; Shaked, Yeala; Schenkeveld, Walter D. C. (Frontiers in Marine Science, 2020)
Desert dust is a major source of iron (Fe) to Fe-limited ocean regions. However, Fe-limited phytoplankton often struggle to obtain dust-bound Fe (dust-Fe) due to its low solubility and short residence time in the euphotic zone. Trichodesmium, a globally important nitrogen-fixing, cyanobacterium, is uniquely adapted for utilizing dust as an Fe-source. Trichodesmium can actively collect and concentrate dust particles within the core of its colonies and enhance dust-Fe dissolution rates via two bio-dissolution mechanisms: reduction and complexation by a siderophore. Here, mimicking bio-dissolution in Trichodesmium colonies, we studied the kinetics of desert dust dissolution by a siderophore and a reductant in seawater. By concurrent measurements of dissolved Fe, silica and aluminum we recognized two major mineral pools that released Fe into seawater over an 8-day period: Fe(hydr)oxides and aluminosilicates. In the presence of the siderophore desferrioxamine-B, we observed two stages of dissolution: a short stage of fast Fe dissolution followed by a lasting stage of slow Fe dissolution that was highly correlated to aluminum and silica dissolution. In the presence of the reductant, ascorbate, Fe dissolution was not correlated to aluminum and silica dissolution and was relatively slow. Based on these observations and on dust minerology, we constructed a conceptual model for dust-Fe dissolution by a siderophore and a reductant from two major mineral pools: reductive and siderophore-promoted dissolution of Fe(hydr)oxides and slow continuous dissolution of Fe-bearing clays in the presence of a siderophore. Our findings highlight the importance of clays as an Fe source to Trichodesmium and possibly to marine phytoplankton in general and can be further used to assess the contribution of dust-Fe to the Fe requirements of natural Trichodesmium colonies. From our measured bio-dissolution rates and concentrations of dust retained within colonies from the Gulf of Aqaba, we calculated the supply of dissolved Fe from dust to Trichodesmium. Based on published Fe-quotas and growth rates we calculated Trichodesmium’s Fe requirements under Fe-limited and Fe-replete conditions. The calculated dissolved Fe supply from dust, retained by a colony, can fulfil the minimal Fe requirements of slow growing, Fe-limited colonies, but cannot support fast growth and/or higher cellular Fe quotas.